Iron Resources and Productions for the Roman Frontier in Pannonia - Durman, Aleksandar (1998)
In the period from the second to the fourth century A.D. an amount of iron exceeding 750.000 tons (in bars and blooms) was transported through Siscia and most process there - mostlikely aimed towards meeting the needs of the Roman frontier.
Projekt MZOS
ENG